Harmony Analysis through Components, Substitution-Inversion Chord, Suspension Tone and Song Structure "Easy On Me" Version of Group Scary Pocket - Hadi, Randi Restu; Sinaga, Friska Br; Rahmadinata, Melisa Fitri (Scoring: Journal of Film Music, 2024)
Arranging popular music has several tips in its realization process, including the application of substitution chord, inversion chord and suspension tone. The are similarities in several techniques used in arranging if we dissect them based on the process of creating a new work, only in arranging, the arranger immediately focuses his imagination on the basic elements of music that already exist for further modification. Meanwhile, the difference in creating new work is actualize first some of the basic elements of the music wich are then developed. Scary Pocket is a music group that is intense in arranging music by applying methods of modifying the structure and harmony of songs so that it has an impact on the creation of their version of a new musical style. Through this simple article, it is hope that it can become a reference for art activist and arranger in determining the tips that will be used in arranging the piece of music.Keywords: substitution chord, inversion chord, easy on me, scary pocket